How Does Different Cropland Expansion Trajectories Affect Cropland Fragmentation? Insights From Three Urban Agglomerations in Yangtze River Economic Belt, China - Wang, Liye; Zhang, Siyu; Xie, Yifan; Liu, Yanfang; Liu, Yaolin (Frontiers in Ecology and Evolution, 2022)
A clear understanding of cropland expansion dynamics and their effects is vital for cropland protection and food security. However, the trajectories of cropland expansion have been less discussed. This study referred to the modes of landscape expansion and assessed the cropland expansion trajectory in three urban agglomerations in the Yangtze River Economic belt and its impact on cropland fragmentation. Specifically, we identified three cropland expansion trajectories using the landscape expansion index: infilling, edge-expansion, and outlying trajectory. Moreover, the surface relief amplitude model was employed to characterize the relief amplitude effect on cropland expansion trajectories. By coupling landscape metrics (e.g. patch density, landscape shape index, the largest patch index, and aggregation index) and Spearman correlation analysis, the relationship between cropland expansion trajectories and cropland fragmentation was assessed. Results show: (1) Three urban agglomerations experience cropland expansion, in which the edge-expansion trajectory is primary, followed by infilling and outlying trajectories; (2) The cumulative frequency curve indicates that infilling and edge-expansion trajectories are likely to distribute in low topographic relief amplitude, while the outlying trajectory locates in relative higher topographic relief amplitude regions; (3) Infilling and edge-expansion trajectories contribute a significantly positive relationship with the decrease of cropland fragmentation, while the outlying trajectory has a negative relationship with cropland fragmentation. This research highlights that cropland protection policies should considerably focus on the trajectory of cropland expansion, not only requests the total area of cropland in a dynamic balance.